KADAR PROKSIMAT CAKALANG ASAP YANG DI PROSES DENGAN BEBERAPA JENIS KAYU BAKAR DAN METODE PENGASAPAN - Naema Bora; Agripina Agnes Bele (Partner, 2019)
This study aimed to obtain the type of firewood as a natural preservative and the best smoking method to produce high-quality smoke Cakalang with longer durability. This study uses an experimental method designed in a completely randomized design (CRD) factorial pattern of 3x2, with two factors namely the type of firewood and the smoking method. The main variables collected in this study are, pH, water content, protein content, fat content, ash content and calcium of smoke Cakalang. The monitoring period is carried out on days 0, 3, 6 and 9 days of storage. The results showed that, in general, smoke Cakalang products were initiated by using firewood and the smoking method gave the best effect on pH, water content, protein content, fat content, ash content and carbohydrate content. The use of firewood from kusambi wood and coconut shell can increase the durability of fish for up to 9 days of storage. Kusambi wood and coconut shell have good potential for firewood because they can increase the levels of protein, carbohydrate, fat content, and decrease of pH, water content and ash content of smoke Cakalang. The smoking method using a closed smoking cabinet produces betterquality of smoke cakalang compared to an open cabinet. Keywords: Firewood type, smoking method, durability, proximate content of smoke Cakalang